Influence of hormones and medium components on expression of dipyranocoumarins in cell suspension cultures of calophyllum inophyllum L. - Pawar, Kiran D.; Thengane, Shubhada Ratnakar (Process Biochemistry, 2009)
Cell suspension cultures were initiated separately from leaf and nodal/internodal calluses for the study of influence of hormones and medium components on biomass growth and expression of dipyranocoumarins. Highest 6.2 times biomass was enhanced in suspension cultures of nodal/internodal callus supplemented with threefold total sulphate. Picloram 8.28 mu M along with BAP 8.88 mu M enhanced 295.05 times inophyllum A in suspension cultures of leaf callus whereas IBA 14.70 mu M along with BAP 4.44 mu M in suspension cultures of leaf callus enhanced 1065 times inophyllum B. IBA 4.90 mu M alone in suspension cultures of nodal/internodal callus enhanced maximum 616 times inophyllum C. Only IBA 9.80 mu M in suspension cultures of leaf callus enhanced 23.22 times inophyllum P. Variation in nitrate and sulphate had maximum positive influence on expression of inophyllums A and C and vitamins had maximum positive influence on expression of inophyllums A, C and B. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Calophyllum inophyllum; dipyranocoumarins; Expression pattern; HPLC; Medium components; Suspension culture